Ultra High Molecular Weight NORDEL™ EPDM for TPV and Low Hardness Molded Goods Enabled by Advanced Molecular Catalyst. (June 2019) - Wu, S.; Han, T.; Thakur, V.; Weeks, R.; Li Pi Shan, C.; Tuberquia, J.
Abstract: Ethylene propylene diene synthetic rubber (EPDM) is the material of choice to manufacture various automotive parts due to its natural stability and resistance to heat, UV, and ozone. In addition, its polyolefinic nature results in consistent processing and good filler and oil acceptance for use in compounds ranging from automotive weather sealing, under-the hood belts and coolant hoses, roofing membranes, gaskets and other general rubber articles. Building on a fifty-year history of performance, Dow's Advanced Molecular Catalyst (AMC) and process technology advancements enable highly tailored design of EPDM molecular architecture including, composition, molecular weight and long chain branching (LCB). This is not only resulting in capacity efficiency and sustainable production but also increasing design options of the molecular features to tailor the performance for high in-use efficiency. This paper summarizes a new ultra high molecular weight (UHMW) NORDEL™ EPDM product and its potential applications. Case studies will be presented to showcase its use in thermoplastic vulcanizate (TPV), black color low hardness compounds, and lighter color (gray) washing machine gasket application. The EPDM polymer structure, compound formulation, mixing performance, compound rheology, vulcanization characteristics, and mechanical property improvements are discussed.